Acetylcholine Neurotransmitter Receptor Densities in the Striatum of Hemiparkinsonian Rats Following Botulinum Neurotoxin-A Injection - Mann, Teresa (Front Neuroanat, 2018)
Cholinergic neurotransmission has a pivotal function in the caudate-putamen, and is highly associated with the pathophysiology of Parkinson's disease. Here, we investigated long-term changes in the densities of the muscarinic receptor subtypes M(1), M(2), M(3) (mAchRs) and the nicotinic receptor subtype α(4)β(2) (nAchRs) in the striatum of the 6-OHDA-induced hemiparkinsonian (hemi-PD) rat model using quantitative in vitro receptor autoradiography. Hemi-PD rats exhibited an ipsilateral decrease in striatal mAchR densities between 6 and 16%. Moreover, a massive and constant decrease in striatal nAchR density by 57% was found. A second goal of the study was to disclose receptor-related mechanisms for the positive motor effect of intrastriatally injected Botulinum neurotoxin-A (BoNT-A) in hemi-PD rats in the apomorphine rotation test. Therefore, the effect of intrastriatally injected BoNT-A in control and hemi-PD rats on mAchR and nAchR densities was analyzed and compared to control animals or vehicle-injected hemi-PD rats. BoNT-A administration slightly reduced interhemispheric differences of mAchR and nAchR densities in hemi-PD rats. Importantly, the BoNT-A effect on striatal nAchRs significantly correlated with behavioral testing after apomorphine application. This study gives novel insights of 6-OHDA-induced effects on striatal mAchR and nAchR densities, and partly explains the therapeutic effect of BoNT-A in hemi-PD rats on a cellular level.